Implementation of Participatory Training Model to Develop Teachers' Ability to Design Formative Assessment Instruments in Science Learning - Muslim Muslim*; Nuryani Y Rustaman; Parsaoran Siahaan; Winny Liliawati; Ridwan Efendi (Universitas Syiah Kuala, 2023)
Formative assessment is an essential aspect of learning. Facts in the field show that there still needs to be more teachers who conduct formative assessments during the learning process. The assessment that carries out assesses the final results of learning through summative. This study aims to analyze the ability of science teachers to design formative assessment instruments in science teaching through the implementation of the participatory training model. The research method used is descriptive research with a quantitative approach. The research subjects were 30 junior high school science teachers in Sumedang Regency. Data collection instruments are formative assessment product sheets made by teachers and questionnaires. Data analysis techniques include data reduction, presentation, and conclusion drawing. The results showed that the ability of teachers to design formative instrument assessments was categorized as good. Teachers can create formative instrument assessments integrated into science learning in a varied manner. Teachers' responses to the strengthening and mentoring